1972
DOI: 10.1002/app.1972.070160915
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structural effects of halogen and phosphorus polyol mixtures on flame retardancy of flexible polyurethane foams

Abstract: synopsisThe role of mixtures of reactive bromine and phosphorus flameretardant polyol intermediates as well as the individual bromine and phosphorus reagents in suppressing combustion of flexible polyurethane foams was investigated by means of the oxygen index flame test and charring techniques. Bromine alone appears to contribute to flame retardancy in the solid as well as the vapor phase. A substantid portion of the bromine from both aliphatic and aromatic bromide flame retardants w q accounted for in the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 3 publications
3
17
0
Order By: Relevance
“…Polyols based on phosphates were found to be more effective as flame retardants in urethane and isocyanurate-urethane foams than polyols based on phosphonates. Similar results were reported for flexible urethane foams by Papa and Proops [76] and for cotton by Arney [77]. At phate-based polyols decompose faster than phosphonate into catalytically active species, which catalyze char formation.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Polyols based on phosphates were found to be more effective as flame retardants in urethane and isocyanurate-urethane foams than polyols based on phosphonates. Similar results were reported for flexible urethane foams by Papa and Proops [76] and for cotton by Arney [77]. At phate-based polyols decompose faster than phosphonate into catalytically active species, which catalyze char formation.…”
Section: Methodssupporting
confidence: 89%
“…It was found that results of other authors obtained for flexible foams [76] and cotton [77] can be linearized by the same method ( Figure 3) and thus the effect of the phosphorus on the oxygen index values can generally be correlated by the following equation:…”
Section: Methodsmentioning
confidence: 92%
“…Generally, polyurethanes do not exhibit sufficient flame retardancy and are easily burned. Therefore, emphasis on the development of technologies to promote flame retardancy and create flame‐retardant materials has recently increased 2–4. Among these materials, organophosphorus compounds, which generate negligible amounts of toxic gas and smoke, have demonstrated high efficiency as flame retardants for polyurethane.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Some authors consider two modes of interaction, the first being a physical interaction observed in the combination of ammonium polyphosphate and hexabromocyclododecane within polyacrylonitrile. 8 An alternative physical interaction is suggested to occur in flexible polyurethane formed from bromine and phosphorus-containing polyols, 9 where it has been observed that the bromine system does not act in the gas phase as a radical trap (as would typically be expected) but as a blowing agent thus producing a foamed char. A second postulated mode suggests some form of chemical interaction of phosphorus and bromine when present either in the same or separate molecules.…”
Section: Introductionmentioning
confidence: 98%